Thermosensitive development and tip regulation in a mutant of Dictyostelium discoideum. - Barclay, S L (1982)
A thermosensitive developmental mutant of Dictyostelium discoideum identifies a gene product that is nonessential for cell multiplication but is continuously required during aggregation and the period when multicellular mounds are formed. After mounds form a tip, which has the properties of an embryonic organizer, this gene product may be nonessential. Surgical removal of the tip from a polarized developing multicellular structure (the slug) leads to emergence of a new tip at the permissive temperature but not at the restrictive temperature. The mutant continues to develop abnormally when mixed with wild-type cells; therefore, a cell-limited rather than an exchangeable factor is altered. Assays show that the mutant has a thermosensitive defect in chemotaxis toward cAMP. The mutation reduces the number of cell surface cAMP receptors expressed at the restrictive temperature without affecting their dissociation constants or their apparent thermostability. The expression of two developmentally regulated enzymes, N-acetylglucosaminidase and cAMP phosphodiesterase, is unaffected by the mutation.